The Effects of Dietary Vitamin E on the Oxidative Stress and Antioxidant Enzyme Activities in Their Tissues and Ovarian Egg Numbers of Freshwater Crayfish Astacus leptodactylus (Eschscholtz, 1823) - Barim, Ozden (Medwell Online, 2009)
The effects of dietary vitamin E on the oxidative stress (lipid peroxidation (as Malondialdehyde (MDA)) and antioxidant enzyme activities (as Glutathione Peroxidase (GSH-Px)) of hepatopancreas, ovarian and muscle tissues and the ovarian egg numbers and size of freshwater crayfish Astacus leptodactylus was investigated. Crayfish were fed daily 2% of their total wet weight with vitamin E supplemented diets and a control for 72 days. The vitamin E contents of the control diet, diet 1-3 were 65.83, 100, 150 and 200 mg kg(-1), respectively. Results showed that diet 2 containing 150 mg kg(-1) supplemental vitamin E was associated with a significant increase (p<0.001) in the number of ovarian eggs (48.68%) of crayfish. In addition, the females fed with diet 2 and diet 3 produced significantly bigger ovarian eggs (10.93 and 5.47%) (p<0.001). It was determined that MDA activity decreased significantly in the hepatopancreas, ovarian and muscles of the crayfish fed with vitamin E supplemented diets. While GSH-Px activity was significantly elevated in the hepatopancreas and muscle by vitamin E, its activity decreased in the ovarian.
Keywords: Astacus leptodactylus; crayfish; vitamin E; ovarian egg; MDA; GSH-Px